Bridging the divide: Reflections on university-industry collaboration for the development of the graduate certificate in petroleum data management. Issue 6 (27th June 2019) - Cousins, Fionnuala; Reid, Peter; Tait, Elizabeth
Abstract : Purpose: The purpose of this paper is to present an analysis of the development of a new graduate certificate course in Petroleum Data Management. The course was developed in response to an identified gap in skills and training in data management that was perceived to be a substantial risk in terms of: industry sustainability, efficiency and potentially wider implications of safety as assets are transferred between operators and for decommissioning. The aim of this paper is to critically reflect on how academia and industry can work together to support emerging professions in information management. Design/methodology/approach: The paper draws on observations and interviews from key stakeholders involved in the course development. Findings: The course development process was ultimately successful but also challenging and lessons have been learned which will be of interest to the wider professional and academic body. These include: securing resources and industry engagement for course development, negotiating cultural differences between academic and industry and managing stakeholder relationships throughout the lifecycle of the course development. Originality/value: The paper demonstrates the challenges and opportunities of developing a university course in collaboration with industry partners. Oil and gas exploration and production is a data-intensive industry but it was only relatively recently that attempts have been made to set industry standards and roles of "data manager" or "data analyst" have been created to manage these. This paper has wider implications for understanding the professionalisation of the nascent data management disciplines and contributes to the ongoing dialogue around the changing library and information science profession.